Pengaruh Penggunaan Lapisan Phase Change Material Parafin Grafit Sebagai Pendingin Terhadap Efisiensi Panel Surya Polycrystalline - Rovida Camalia Hartantrie; Ryann Argadiraksa; I Gede Eka Lesmana (P3M Politeknik Negeri Cilacap, 2022)
Solar panels such as PLTS can be an alternative to complete electricity needs. However, the intensity and temperature of the sun that can not be adjusted are an obstacle to the use of solar panels. Continuous absorption of sunlight can cause solar panels to overheat. Therefore, it is necessary to cool the solar panels, therefore the heat absorbed does not exceed the capacity. Phase Change Material (PCM) paraffin graphite is one of the coolants for solar panels. PCM paraffin graphite was used to coat solar panels and then measured for voltage, current, and temperature. The results were compared with solar panels that were not covered with PCM paraffin graphite. The test results found that solar panels coated with PCM produced a lower surface temperature of 0.1458% than those without PCM. Meanwhile, the efficiency and power produced by PCM-coated solar panels were 19.496% and 0.02685% higher than solar panels without PCM, respectively, so the use of PCM paraffin graphite in solar panels can increase their efficiency.